Democracy Dysfunctions and Citizens’ Digital Agency in Highly Contaminated Digital Information Ecosystems - Juan Herrero; Hazal Dilan Erdem; Andrea Torrres; Alberto Urueña (Societies, 2025)
Social media platforms have been recognized as significant contributors to the dissemination of polarizing content, the spread of disinformation, and the proliferation of far-right populist discourse. While certain political actors deliberately seek to disseminate disinformation, a more nuanced understanding is necessary to elucidate why users consume and accept this biased content. Using data from over 120,000 participants across five European and Spanish surveys, we empirically examined the relationships between social media use, disinformation, false news, users’ digital agency, far-right ideology, and far-right voting. We postulated that a lack of users’ digital agency is a significant contributor to this phenomenon and found a significant association between users’ low digital agency and the adoption of far-right ideologies (odds ratio [OR] = 1.16, 95% confidence interval [CI] 1.08–1.23). This association remained after controlling for trust in social media news, psychological and social factors, sociodemographic variables, and response bias.